ASSOCIATION OF HORMONAL IMBALANCE, LIFESTYLE AND CLINICAL ATTRIBUTES WITH FEMALE INFERTILITY. - Hafiza Faiza1*, Muhammad Rafique Duodpota2, Farheen Shaikh3, Muhammad Rafiq4, Ghulam Murtaza5, Syed Habib Ahmed Naqvi6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
OBJECTIVE: Millions of couples are affected by infertility annually due to several reasons throughout the world. The aim of present study was to evaluate the association between female infertility, hormonal imbalance, lifestyle and clinical attributes. METHODS: The females suffering from infertility were evaluated through different parameters, including hormones (FSH, LH, TSH and Prolactin) diet, weight, age, workload, emotions, habits and transvaginal scans (TVS).The findings were compared between fertile and in infertile women. RESULTS: The participants included in this study were 110 infertile females, age 18 to 40 (Mean age ± SD 29 ± 6.78) years. The major group of infertile females (45.5%) was aged 18 to 27 years. Overall 85.5% females were housewives with 79% literacy rate, and the majority of females were either overweight (48.2%) or obese (21.8%). About half of infertile females were very frequently eating junk food including chicken and meat and thus 41.8% of the female got irregular menstrual cycle due to hormonal disturbance. An important association between the level of follicle stimulating hormone, leutinizing hormone, Prolactin, the reproductive age and female’s infertility was observed. About 68-70% infertile females showed imbalance of FSH and LH from borderline to abnormal while TSH and Prolactin were 37-42% from borderline to abnormal. In TVS, 86.4% females showed immature and multiple small sized follicles which were failed to mature enough for ovulation. CONCLUSION: The present research concluded that female diet and lifestyle also play a major role in fertility. The hormonal imbalance for LH, FSH, TSH and Prolactin is significant assumption which causes infertility problem in the studied patients.